대순사상의 남녀평등이념과 여성성 재조명 - 여성해원의 원리로 본 공덕과 실천을 중심으로 - 박민미; 황희연; 박용철; Park, Min-mi; Hwang, Hee-yeon; Park, Yong-cheol (大巡思想論叢, 2017)
This study focuses on reviewing the concepts, roles, meanings, and values ascribed to females and femininity as observable in Daesoon thought and in Feminist theory. Especially with regards to the process of achieving gender equality through the resolution of grievance for females in Daesoon thought, the study draws positive and desirable roles within this practice by specifically examining good deeds performed by females and practical roles that females play. By doing so, this study finds a way to go from the world of mutual contention to the world of resolving grievances that have arisen due to the oppression of yin and the encouragement of yang. First wave feminism can be summarized as the inclination for equality. In Daesoon thought concerning this and from standpoint of females, the most ideal image of woman is one of a female Perfected Being who is unified with Dao and has thereby achieved perfection of her humanity apart from gender. In the Later World (Hucheon), people can get results based on their hard work regardless of gender. The enlightenment of Dao is such that it is not important to distinguish between males and females. Both of them can be 'unified with dao'. Therefore, despite the similarity, the concepts of equality in first wave feminism and the resolution of grievance for women have differences in terms of their ideal vision of equality. The representative claim in second wave feminism is 'consideration' and, in this context, 'consideration' has pronounced feminine characteristics. In Daesoon thought, this sense of 'consideration' is related to the concept of 'Jamojijeong', a term that refers to motherly affection. However, it is not simply a virtue of females and mothers, but rather the value of 'Yin (pronounced in Sino-Korean as 'Eum')' called 'Eumdeok (hidden virtue)'. Jamojijeong means that people should behave in a modest way and this helps them achieve their aims. It is also closely related with 'femininity' in the sense of Eum. One of processes spreading it socially is to propagate virtue (Podeok) and if harmony is achieved through it, then 'right yin and right yang' emerge as the precondition by which Pyeong Do (Pacification of Tao) can be realized. Furthermore, because the aspect of Pyeong is a cosmic process, it has distinct differences from the social aims of feminism and the worldly aims of other numerous ideologies. In proceeding from the Former World (Seoncheon), an era of mutual contention, to the Later World, an era of mutual beneficence, it is essential to emphasize the connection between 'harmony (Hwa)' and 'propagating virtue' as the starting point from which the perspective of Daesoon thought aiming at the principle of 'Pyeong' and 'Hwa' emerges. Herein one can discover that the realization of Daesoon thought is based on the vitalization of the feminine value of 'Jamojijeong'. 본 연구의 목적은 대순사상에 입각한 여성성(女性性)과 외부담론인 페미니즘(Feminism) 이론을 통해 여성과 여성성에 대한 개념 및 그 역할의 의미와 가치를 재조명해보고자 하는 데 있다. 특히 남녀평등 이념을 실현하는 과정에서 대순사상의 여성해원(女性解冤)과 관련하여 여성으로서의 공덕(功德)과 이를 위한 실천적 부분에 대해 집중적으로 살핌으로써 여성해원의 적극적이고 바람직한 역할을 도출하고자 한다. 그럼으로써 상극(相克)의 세계를 상생(相生)의 세계로, 억음존양(抑陰尊陽)의 상황이 낳은 갈등을 정음정양(正陰正陽)할 수 있는 길을 모색하고자 한다. 1세대 페미니즘은 평등 지향 논리로 요약될 수 있다. 이를 대순사상과 관련시켜 볼 때, 남녀를 떠나서 완전한 인간완성을 이루고자 한다면 여성의 입장에서 보았을 때 대순사상에서 제시하는 가장 이상적인 여성상은 여성도통군자(女性道通君子)일 것이다. 후천에서는 남성과 여성의 구별이 없이 노력한 만큼의 결과를 얻을 수 있다. 도의 이치에 대한 깨달음, 즉 음양의 이치를 깨달은 상태에서는 남성과 여성의 구별이 무의미하며 남녀 모두 '도통군자(道通君子)'에 다름 아닌 것이다. 따라서 페미니즘 1세대의 평등이념과 여성해원 사상은 그 개념 구사의 유사성에도 불구하고 평등의 이념이 도달하고자 하는 차원이 명백히 구별되는 논의라고 할 것이다. 2세대 페미니즘의 대표적 논증은 '배려'라는 여성적 특질의 강조이다. 대순사상에서 이와 관련되는 개념은 자모지정(慈母之情)이다. 그런데 자모지정은 비단 여성만이 가지는 덕도 아니고 어머니인 사람만이 가지는 덕이 아니라 '음덕(陰德)'이라고 하는 '음(陰)'의 가치이다. 자모지정은 자신을 적극적으로 내세우는 것이 아니라 낮추고 타인의 뜻을 이루도록 돕는 실천 영역을 지칭하며, 음(陰)이라는 원리의 환유적 차원인 '여성성'과 닿아있는 가치이다. 이를 사회적으로 확산시키는 과정 중에 하나로써 중요한 것이 포덕이라고 할 수 있으며, 이러한 포덕을 통해 화(和)를 이끌어내면 '정음정양'이라는 도가 실현된 평(平)의 상태에 도달할 수 있는 것이다. 그리고 이 평의 차원은 정음정양이 실현된 우주적 과정이기 때문에 단순히 사회에서의 평등 구현이라는 페미니즘, 혹은 다수의 이데올로기들의 세간적 차원의 목표와 명백한 차이를 가지고 있다. 상극의 시대인 선천에서 상생의 시대인 후천으로 나아감에 있어서 '평(平)'의 원리와 '화(和)'의 원리를 부단히 실천해가야 한다는 논리를 제시한다고도 볼 수 있는 대순사상의 관점에서 그 출발점에 있는 '화(和)'와 '포덕(布德)'의 관계성과 그 가치에 대한 강조가 중요하다고 할 때 대순사상의 실현은 '자모지정'이라는 여성적 가치의 활성화에 그 출발점이 있다고 밝힐 수 있다.